Reimagining Prosperity - Bartl, Marija (Cambridge University Press, 2025)
Articulates why the EU is well-placed to articulate and institute a new vision of prosperity that is both credible and appealing, whilst further fostering caring consumption, circular economy, sustainable industry and fairer corporate activity. This title is also available as Open Access on Cambridge Core.